Health-related quality of life (HRQoL) in patients (pts) with progressive, poorly differentiated, extra-pulmonary neuroendocrine carcinoma (PD-EP-NEC) enrolled in NET-02: A phase II trial of liposomal irinotecan (nal-IRI)/5-fluorouracil (5-FU)/folinic acid or docetaxel as second-line therapy. Issue 28 (1st October 2022) - Craig, Zoe; Swain, Jayne; Sharma, Rohini; Faluyi, Olusola Olusesan; Wadsley, Jonathan; Morgan, Carys; Wall, Lucy R.; Chau, Ian; Reed, Nicholas Simon; Sarker, Debashis; Margetts, Jane; Krell, Daniel; et al.
Abstract : 293 Background: NET-02 was a multi-centre, randomised (1:1), non-comparative phase II trial of nal-IRI/5-FU/folinic acid (ARM A) or docetaxel (ARM B) in pts with progressive PD-EP-NEC, aimed at selecting a treatment for evaluation in a phase III trial. Primary analysis (N = 58) showed ARM A, but not ARM B, achieved the target 6-month progression-free survival rate primary endpoint (McNamara et al. ASCO 2022). HRQoL was a secondary endpoint in NET-02. Methods: HRQoL was assessed using the EORTC QLQ-C30 and GINET21 (at baseline (BL), 6-weekly intervals and at disease progression). The mean change from BL was estimated for each scale by timepoint and treatment arm. Results are presented where there were ≥4 responses per time point. Scores were considered stable if they did not change by > 10 points from BL. The mean BL C30 scores for all pts were compared to United Kingdom (UK) population normative C30 data using a 2-sample t-test. Results: Fifty-four of 58 pts (93%) completed a BL questionnaire; of these, 39 (72%) completed ≥1 post-BL questionnaire, with 21 (51%) completing questionnaires at progression. Global health status (GHS) and all functional scales in ARM A remained stable from BL to intervals pre-progression, with a sustained improvement in role functioning observed post-BL. In ARM B, GHS and all C30 functional scales decreased by > 10 points between BL and week 18 (worsening of QoL). Both arms had a > 10-point increase from BL in constipation and diarrhoea in ≥1 post-BL time point. In ARM A, pain, insomnia and financial problems decreased from BL. No C30 symptom scales in ARM B were consistently lower post-BL. Patterns of change in GINET21 mean score were similar in both arms: body image, disease-related worries, information/communication, sexual function and social function all had a > 10-point reduction in score from BL (indicating improvement in symptoms/problems); endocrine and gastrointestinal symptoms remained stable; muscle/bone pain varied across time points, initially showing a reduction in pain followed by an increase, compared to BL. In comparison to the UK C30 norms (BL all pts), 11 of 15 C30 scales did not significantly differ (P > 0.05). Mean scores for fatigue and appetite loss were significantly higher than UK C30 norms (worse symptoms in pts from NET-02) (P = 0.03, P = 0.0003 respectively). However, emotional functioning and GHS were significantly better in pts from NET-02 (P = 0.001, P = 0.03 respectively). Role and social functioning were lower in pts from NET-02 (both P = 0.06) (poorer level of functioning). Conclusions: HRQoL was maintained and potentially improved with nal-IRI/5-FU/folinic acid, but not docetaxel. Compared to the UK general population, BL QoL did not substantially differ in pts from NET-02. Clinical trial information: NCT03837977.